Global guide to medical information - Kurian, George Thomas 1931- (Elsevier, 1988)
"Sourcebook on resources, programs, and institutions dealing with medical research and practice throughout the world." Contains national, regional, and international organizations, also covering the medical media and the communications industry. Arranged under international and regional organizations; research institutes; national associations by subjects; medical publishers; online databases; indexes, bibliographies, and statistics; symposia and conference series; and periodicals. General index.